2010
DOI: 10.1038/pj.2010.112
|View full text |Cite
|
Sign up to set email alerts
|

Alternating copolymerization of CO2 with propylene oxide and terpolymerization with aliphatic epoxides by bifunctional cobalt Salen complex

Abstract: A novel N,N¢-[2,2¢-bis(nitrilomethylidyne)]bis[a-methyl-4-(morpholin-1-ylmethyl)-6-tert-butyl phenolato]-1,2-diaminocyclohexane Co III (2,4-dinitrophenoxy) complex (complex 1) was designed and used to couple carbon dioxide (CO 2 ) and propylene oxide (PO) as a single-component catalyst. Systematic investigation revealed that complex 1 was highly active and selective in the coupling of CO 2 /PO and that complete consumption of PO was accomplished with high copolymer selectivity. A high molecular weight of up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Surprisingly in this study, the weight percentage of the cyclic carbonate in the product was found to decrease with increasing reaction temperature. This is in contrast with the report mentioned elsewhere where stated that the formation of thermodynamically stable cyclic carbonate is highly favored at higher reaction temperature (Li and Niu, 2011). Another important finding was that the signal of ether unit becomes more significance at higher reaction temperature (Supplementary A3).…”
Section: Analysis Of Productscontrasting
confidence: 89%
“…Surprisingly in this study, the weight percentage of the cyclic carbonate in the product was found to decrease with increasing reaction temperature. This is in contrast with the report mentioned elsewhere where stated that the formation of thermodynamically stable cyclic carbonate is highly favored at higher reaction temperature (Li and Niu, 2011). Another important finding was that the signal of ether unit becomes more significance at higher reaction temperature (Supplementary A3).…”
Section: Analysis Of Productscontrasting
confidence: 89%
“…The area of catalyst development brings together the fields of organometallic and polymer chemistry. This review has highlighted the development of catalysts from the early days of the field, when zinc alkoxide and carboxylate clusters were the mainstay of research, through the development of successful single-site metal complexes, and beyond to the study of kinetics and [15,38,93,179] mechanism to inform the preparation of the current bimetallic catalysts. These mechanistic studies have implicated bimetallic active sites in many cases, although there do remain other examples where monometallic mechanisms appear dominant, most notably for metal porphyrins used with cocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Variation of the polymer properties can also be achieved by terpolymerization of cyclohexene oxide (CHO) and PO with carbon dioxide (CO 2 ) . In contrast to the brittle behavior of PCHC (elongation at break of 1–2%), PPC exhibits higher flexibility (elongation at break between <10 and 1200% with a median around 600% depending on the used catalyst and polymerization conditions), but its low T g (30–40 °C) clearly limits its use .…”
Section: Functional Ethylene‐oxide‐based and Terminal Epoxide Monomersmentioning
confidence: 99%